Russian Perceptions of U.S. Lawyers as a Lingual-Cultural Type - Evgenia Gulyaeva (TEFLIN Journal: A publication on the teaching and learning of English, 2008)
This article introduces the reader to the theory of a lingual-cultural personality and lingual-cultural types in particular. A lingual-cultural type is a generalized image of personalities whose behavior and values significantly influ-ence the culture in general and is a representative of ethnic and social variety of the society. The type of an American Lawyer is being analyzed, because in the United States of America, unlike any other country, the role of a lawyer has a pervasive shared understanding. The author examines how lawyers are repre-sented in US popular culture, specifically exploring presentations in legal and crime fiction. She also analyzes results from a survey of 100 Russian students, exploring their perceptions of the lingual-cultural type of US lawyers